2010
DOI: 10.1155/2010/325183
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Changes Induced by PPAR Gamma Agonists in Animal and Human Liver

Abstract: Thiazolidinediones are a class of Peroxisome Proliferator Activated Receptor γ (PPARγ) agonists that reduce insulin resistance in type 2 diabetic patients. Although no detectable hepatic toxicity has been evidenced in animal studies during preclinical trials, these molecules have nevertheless induced hepatic adverse effects in some treated patients. The mechanism(s) of hepatotoxicity remains equivocal. Several studies have been conducted using PCR analysis and microarray technology to identify possible target … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(81 citation statements)
references
References 90 publications
2
75
0
4
Order By: Relevance
“…Rosiglitazone is a known mild PXR inducer (Sinz et al, 2006); however, if rosiglitazone was operating through the PXR receptor, then rifampin should have induced mRNA as well. Rosiglitazone is potentially binding and inducing CYP2J2 through peroxisome proliferator-activated receptor (PPAR), which also induces mRNA of CYP2B and CYP4 enzymes (Rogue et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Rosiglitazone is a known mild PXR inducer (Sinz et al, 2006); however, if rosiglitazone was operating through the PXR receptor, then rifampin should have induced mRNA as well. Rosiglitazone is potentially binding and inducing CYP2J2 through peroxisome proliferator-activated receptor (PPAR), which also induces mRNA of CYP2B and CYP4 enzymes (Rogue et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…For native SW872, vector control, and CETP + cells, the expression of these transcription factor genes followed the same order: CEBP ␤ > PPAR ␥ > CEBP ␣ . The expression of SREBF1 , a master regulator of lipid synthesis, was unchanged, and the expression of PPAR ␥ target genes such as PNPLA2 , FASN , and APOE ( 28,29 ) was not different in CETP + cells ( Table 2 ). SCL2A4 and FABP4 levels were reduced by about half.…”
Section: Perilipin Western Blotsmentioning
confidence: 99%
“…Also, TZDs which are strong insulin sensitizers' drugs, act via PPARγ agonism [13,14]. Besides TZDs ben ficial effects in diabetes there are some deteriorating effects following TZDs administration which include hepatotoxicity and hepatic failure [25]. Our results showed that PPARγ gene expression eleva ted by L-carnitine supplementation in diabetic rats, therefore L-carnitine exerts insulin-sensitizing effects by upregulation of PPARγ.…”
Section: T a B L E 2 Body Weight Glucose Insulin And Adiponectin mentioning
confidence: 56%